Microenvironment‐induced restoration of cohesive growth associated with focal activation of P‐cadherin expression in lobular breast carcinoma metastatic to the colon - Malte Gronewold; Isabel Grote; Stephan Bartels; Henriette Christgen; Leonie D Kandt; Maria Jose Brito; Gàbor Cserni; Maximilian E Daemmrich; Franz Fogt; Burkhard M Helmke; Natalie terHoeve; Corinna Lang‐Schwarz; et al. (Wiley, 2024)
Abstract Invasive lobular carcinoma (ILC) is a special breast cancer type characterized by noncohesive growth and E‐cadherin loss. Focal activation of P‐cadherin expression in tumor cells that are deficient for E‐cadherin occurs in a subset of ILCs. Switching from an E‐cadherin deficient to P‐cadherin proficient status (EPS) partially restores cell-cell adhesion leading to the formation of cohesive tubular elements. It is unknown what conditions control EPS. Here, we report on EPS in ILC metastases in the large bowel. We reviewed endoscopic colon biopsies and colectomy specimens from a 52‐year‐old female (index patient) and of 18 additional patients (reference series) diagnosed with metastatic ILC in the colon. EPS was assessed by immunohistochemistry for E‐cadherin and P‐cadherin. CDH1/E‐cadherin mutations were determined by next‐generation sequencing. The index patient's colectomy showed transmural metastatic ILC harboring a CDH1/E‐cadherin p.Q610* mutation. ILC cells displayed different growth patterns in different anatomic layers of the colon wall. In the tunica muscularis propria and the tela submucosa, ILC cells featured noncohesive growth and were E‐cadherin‐negative and P‐cadherin‐negative. However, ILC cells invading the mucosa formed cohesive tubular elements in the intercryptal stroma of the lamina propria mucosae. Inter‐cryptal ILC cells switched to a P‐cadherin‐positive phenotype in this microenvironmental niche. In the reference series, colon mucosa infiltration was evident in 13 of 18 patients, one of which showed intercryptal EPS and conversion to cohesive growth as described in the index patient. The large bowel is a common metastatic site in ILC. In endoscopic colon biopsies, the typical noncohesive growth of ILC may be concealed by microenvironment‐induced EPS and conversion to cohesive growth.